Physical simulation of interfacial microstructure evolution for hot compression bonding behavior in linear friction welded joints of GH4169 superalloy. (15th August 2016) - Yang, Xiawei; Li, Wenya; Feng, Yan; Yu, Siqi; Xiao, Bo
Abstract: In order to carry out the physical simulation of interfacial microstructure evolution for hot compression bonding behavior in linear friction welded joints of GH4169 superalloy, the novel hot isothermal compression bonding tests were performed on a Gleeble-3500 thermal simulator in the temperature range of 970 °C to 1150 °C and at the strain rate range of 0.01 s − 1 to 10 s − 1 . The macroscopic morphology of hot compression GH4169 bonded joints at different parameters were observed by the optical microscope (OM). The interfacial microstructure evolution in the hot compression bonded joints of GH4169 superalloy were investigated by the OM and the scanning electron microscope (SEM). FEM simulation of the hot compression bonding process was given in this paper. The defects in the joints interface were observed by SEM, and the interfacial oxidation of the compression bonded joints was discussed. Graphical Abstract: Highlights: Three types of macroscopic morphology of the bonded joints were distinguished. The microstructure of the bonded joints was observed. The defects in joints interface were analyzed. Temperature has a key influence on the oxygen content in joints interface.